2021
DOI: 10.1002/adtp.202100058
|View full text |Cite
|
Sign up to set email alerts
|

Thiophene Derivative‐Loaded Nanoparticles Mediate Anticancer Activity Through the Inhibition of Kinases and Microtubule Assembly

Abstract: Different tetrahydrobenzo[b]thiophene derivatives are explored as new tubulin polymerization destabilizers to arrest tumor cell mitosis. A series of compounds incorporating the tetrahydrobenzo[b]thiophene scaffold are synthesized, and their biological activities are investigated. The cytotoxicity of each of the synthesized compounds is assessed against a range of cell lines. Specifically, the benzyl urea tetrahydrobenzo[b]thiophene derivative, 1-benzyl-3-(3-cyano-4,5,6,7-tetrahydrobenzo[b]thiophen-2-yl)urea (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Somaya et al designed a series of 2‐aminotetrahydrobenzo[ b ]thiophene derivatives as inhibitors of WEE1 kinase and microtubule assembly. [ 95 ] The cytotoxicity assay demonstrated that compound 28 having the benzyl urea moiety is the most potent with broad‐spectrum anticancer activity against various cancer cell lines where dose‐dependent G2/M accumulation and A549 cell cycle arrest are the possible mechanism of action with apoptosis indicated by the increased levels of caspase 3 and 9. Furthermore, compound 28 inhibits WEE1 kinase and targets tubulin by inhibiting its polymerization.…”
Section: ‐Aminothiophenes and Their Fused Analogs As Anticancer Agentsmentioning
confidence: 99%
“…Somaya et al designed a series of 2‐aminotetrahydrobenzo[ b ]thiophene derivatives as inhibitors of WEE1 kinase and microtubule assembly. [ 95 ] The cytotoxicity assay demonstrated that compound 28 having the benzyl urea moiety is the most potent with broad‐spectrum anticancer activity against various cancer cell lines where dose‐dependent G2/M accumulation and A549 cell cycle arrest are the possible mechanism of action with apoptosis indicated by the increased levels of caspase 3 and 9. Furthermore, compound 28 inhibits WEE1 kinase and targets tubulin by inhibiting its polymerization.…”
Section: ‐Aminothiophenes and Their Fused Analogs As Anticancer Agentsmentioning
confidence: 99%
“…Plates were then incubated at 37°C with 5% CO 2 for 48 hours. Next, Cell Titer 96 aqueous MTS reagent [3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyltetrazolium bromide, purchased from Promega Corporation, San Luis Obispo, CA] was added to the cells following the manufacturer's instructions (63,(68)(69)(70). After incubation for 2 hours, cell viability (%) was calculated on the basis of the absorbance measured at 490 nm using a SpectraMax Plus spectrophotometer (Molecular Devices, San Jose, CA).…”
Section: Cytotoxicity Studymentioning
confidence: 99%
“…Indeed, many heterocyclics bearing thiophene (e.g., AZD-7762, OSI-930, and PF-4989216) have been known to target cancer-specific proteins, leading to inhibition or activation of specific signaling pathways in cancer cells [13][14][15][16][17][18][19]. Another thiophene-bearing drug, nocodazole, has been shown to have antimitotic effects by binding to tubulin and arresting the cell cycle at the G2/M phase [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…13 C NMR spectrum (DMSO-d 6 ), showed several carbon signals at δ C 14.3 ppm (CH 3 ), 15.1 ppm (CH 3 ),19.8 ppm (CH 3 ), 55.3 ppm (O-CH 3 ), and 60.7 ppm (CH 2 ). Furthermore, the signals for aromatic carbon atoms were indicated by their chemical shifts at δ C 113.8 ppm (2C), 116.1, 121.9 ppm (2C), and 157.7 ppm.…”
mentioning
confidence: 99%